The effectiveness of risk management system and firm performance in the European context - Ghazieh, Louai (2021)
Purpose. The purpose of this paper is to study the effectiveness of the risk management system in the European context, especially with regard to the risk management committee, the uncertainty of the environment and company performance. In summary, it evaluates European companies listed on the stock exchange in France, Germany and the United Kingdom to determine how risk management systems influence financial companies' performance. Design/methodology/approach. To study the effectiveness of risk management systems and their influence on performance, the large companies selected in our sample are fairly representative of the European market, according to the Dutch indices of each country (SBF 120 in France, HDAX 110 in Germany and FTSE 100 in United Kingdom).The empirical evidence is based on an international quantitative analysis, using a data set involving 320 companies listed on the stock exchange over a ten-year period from 2005 to 2014. Findings. The results indicate that the establishment of a risk management and control system by a company positively influences its management, and its performance level and value creation also improve. The results of this study demonstrate a significant strengthening of the role of the risk management committee in the three countries. The surveillance function is reinforced, and in particular, the internal control system is accentuated. Research limitations/implications. This study has some limitations that can form leads for future research. One of these limitations is the sample size. The authors have represented the European context by three countries that certainly constitute great European powers, but have regulations different from other countries. The company size is also a possible research element. Indeed, risk management system varies between large, small and medium-sized enterprises, so it is important to study each type of company well. Originality/value. This study identifies the risk management committee as a mechanism of control that is highly important in the company, and it proposes an international framework that comparatively and empirically evaluates how the risk management system used in large European companies can improve their financial performance.